A Closer Look at Implementation Science - Rojas-Andrade, R (Nova Science Publishers, Inc., 2024)
These pages are a testament of Latin American implementation science and our effort to share our findings and practices with researchers from other places on the planet. This book presents a set of people that produce and transform knowledge, and it gives voice to other approaches to implementation science that, paradoxically, lack establishment and replication of scientifically proven interventions in professional practice. It questions the logic of evidence-based research, which seems to blur social experience and mock the concepts of generalization and transformation. Will the Latin American experience be different? Will the gap be more visible from the community approach? Join us to fragment paradigms, to rethink and co-create communities, and not to impose individuality. © 2024 by Nova Science Publishers, Inc. All rights reserved.